Effectiveness of Arbitration as an Alternative Dispute Resolution in Bangladesh - Md. Nazmul Haq; Jannatul Ferdous; Rajib Chandra Das (Department of Government Studies, Universitas Syiah Kuala, 2021)
The structured legal system of Bangladesh is costly and takes a long time to complete. As a result, poor citizens in rural areas can seldom seek justice through the formal judicial process. The costs of hiring a lawyer, the time and money expended in court, and the amount of talent, schooling, and experience needed to litigate all act as roadblocks to justice. As a result, poor people prefer or have no choice but to use conventional justice systems such as Shalish. However, Shalish is a very informal type of local judicial practice that heavily influences rural society’s power structure. With time, people with special interests and musclemen dominate the informal justice system at the village level. Alternative dispute resolution (ADR) had arisen in the Indian subcontinent to improve the village justice system's condition. For the past 35 years, the state-led rural justice system, such as Shalish and village court, has played an essential role in resolving petty rural litigation, but at a sluggish and informal pace. In the evolving landscape of rustic political influence, this age-old court is having difficulty dispensing justice to the countryside citizens. The study looked at the existing rural informal justice systems in Bangladesh, especially the Union Parishad-led ADR, and argued that, if adequately enabled and revamped, this justice system could be a desirable alternative to the formal system of justice for people living in rural areas. The study aimed to recognize the obstacles that the Union Parishad faces in dispensing justice, both directly and indirectly (UP).